CD34 EXPRESSION IN STROMAL TUMORS OF THE GASTROINTESTINAL-TRACT - Mikhael, A. I.; Bacchi, C. E.; Zarbo, R. J.; Ma, C. K.; Gown, A. M. (Lippincott-raven Publ, 1994)
Gastrointestinal stromal tumors (GISTs) are mesenchymal tumors that may exhibit varied morphologic appearances (spindle, epithelioid) and biologic potentials. Given the continuing controversy regarding the type of cell differentiation present in these tumors (muscle versus nerve sheath versus null), we evaluated a set of GISTs, most of which had been previously examined for the presence of smooth muscle differentiation, for expression of CD34, a 115 kDa cell-surface progenitor cell marker also recently identified in a subset of mesenchymal tumors. Using antibody My 10 in deparaffinized, formalin-fixed tissue after pretreatment with microwave energy, we found that 46 of 57, or 81%, of GISTs were CD34+; this fraction of CD34+ tumors exceeded the fraction of these same GISTs found to show muscle actin (72%) expression. In addition, a consistently higher fraction of the tumor cell population was CD34+ than was muscle actin positive. These findings suggest that CD34 is a very sensitive marker for the identification of GISTs. CD34 is normally expressed by endothelial as well as perivascular cells, perhaps related to, but distinct from, vascular smooth muscle cells. While the nature of these latter cells is uncertain, the expression of CD34 in such a large fraction of GISTs may provide evidence of a unique differentiation pathway in these tumors.
Keywords: CD34; IMMUNOHISTOCHEMISTRY; GASTROINTESTINAL STROMAL TUMORS; MUSCLE ACTIN